2014
DOI: 10.3357/asem.3687.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Models of Simulated Moon and Mars Gravities: Head-Up Tilt vs. Lower Body Unweighting

Abstract: Bodyweight unloading via both LBPP and HUT resulted in cardiovascular changes similar to those anticipated in actual reduced gravity environments. The LBPP model/Alter-G has the advantage of providing an environment that allows dynamic activity at reduced bodyweight; however, the significant increase in blood pressures in the Alter-GC may favor the HUT model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Using the lower body positive pressure model, effects for total peripheral resistance were reported to be moderate (Lunar vs. 1 g) and large (Martian vs. 1 g). For thoracic impedance, data published by Kostas et al ( 2014 ) revealed moderate changes in Lunar and Martian gravities compared to 1 g.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Using the lower body positive pressure model, effects for total peripheral resistance were reported to be moderate (Lunar vs. 1 g) and large (Martian vs. 1 g). For thoracic impedance, data published by Kostas et al ( 2014 ) revealed moderate changes in Lunar and Martian gravities compared to 1 g.…”
Section: Resultsmentioning
confidence: 88%
“…For cardiac output as measured using the lower body positive pressure model, Kostas et al ( 2014 ) presented large effects in Lunar and Martian gravity. The effects for cardiac output as measured during head-up tilt revealed moderate changes in Lunar and small changes in Martian gravity compared to 1 g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The only available data, obtained in parabolic flight, headup tilt and lower body unweighting experiments, provided answers to short-term changes from transitioning from 1G to partial gravity levels. [94][95][96] It is critical to understand the physiologic impact of prolonged stays (days to weeks) in reduced gravity levels. What is the minimum level of gravity required to maintain fitness and prevent deconditioning?…”
Section: Incomplete Knowledge About Human Physiology In Partial Gravitymentioning
confidence: 99%
“…The combination of orthostatic stress in normo- and hypovolemic men and women makes this study unique, since most studies, including our previous studies (6, 16), using upright LBPP or HUT simulated only normovolemic activity. Deconditioned physiologic responses (8, 15, 17) to orthostatic stress have been rarely studied, especially in simulating standing on the surface of Moon, the Mars and the Earth.…”
Section: Introductionmentioning
confidence: 99%